Penerapan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (Stad) Untuk Meningkatkan Hasil Belajar Matematika Peserta Didik Kelas 4 C MIN 2 Kota Makassar - Subaedah Subaedah; Akhmad Syahid; Muh. Aidil Sudarmono R; Tirta Inzi Widana (Education and Learning Journal, 2023)
This study examines the Implementation of Supportive Learning Design Types of Student Teams Achievement Division (STAD) in Improving Student Counting Achievement Level 4 C MIN 2 Makassar City. This type of research is quality research located at MIN 2 Makassar City Jl. Pioneer of Independence Km. 15, Daya, Biringkanaya District, Makassar City. The deployment procedures carried out were observation, questions and answers, and archiving. The product of this research shows that the aspects that trigger the decline in arithmetical achievement of students at level 4 C MIN 2 Makassar City include lack of interest, low motivation, lack of teaching aids, frequently changing textbooks, school environment, and family area. Implementation of the Supportive Learning Design Type Student Teams Achievement Division (STAD) was able to increase the arithmetic achievement of students at level 4 C MIN 2 Makassar City by 48% from what initially many students had scores above the KKM amounting to 10 people or 35% increased to 24 people or 83 %. The conclusion of this study is that the factors that trigger the decline in arithmetic achievement of students at level 4 C MIN 2 Makassar City include lack of interest, low motivation, lack of teaching aids, frequently changing textbooks, school areas, and family areas along with the implementation of supportive learning designs of Student Teams. The Achievement Division (STAD) was able to increase the arithmetic achievement of students at level 4 C MIN 2 Makassar City by 48%.